Polski kabaret – tradycja i współczesność - Fox, Dorota (Postscriptum Polonistyczne, 2020)
Polish cabaret, while being inspired by European ancestors, has been evolving over years. It served many purposes, searched for new means of expression. The article presents significant stages of its evolution, which serves as the main context for describing the expansion of contemporary types of cabaret that have been developed under the influence of new media and culture that concentrates on entertainment. Rich cabaret life and significant presence of cabaret programs on TV provokes question concerning the identity of cabaret. An answer to such question enables understanding the reasons of its attractiveness and its presence in different means of popular culture.